Euthanasia in the consciousness of Poles – perception of the problem and cultural changes in Poland - Melon, Jan (The phenomenon of euthanasia: Philosophy – Culture – Medicine – Law, 2025)
The study discusses the issue of euthanasia and the social changes that may affect perceptions of it. After defining the phenomenon of euthanasia and presenting the differences between euthanasia and the cessation of persistent therapy and assisted suicide, the author presents the results of opinion surveys on euthanasia. The following section discusses selected social changes that may have a significant impact on changing Poles’ views on euthanasia.